(untitled) (Journal of Atomic and Molecular Sciences, 2019)
Benzoyleneurea (BenzU), a fluorescent nucleobase analog, exhibits strong solvent dependent fluorescence intensity. With the increasing of the concentration of polar and protic solvents, BenzU exhibits enhanced fluorescence. To understand the photophysical properties of BenzU, the energy gaps (ΔE) between dark nπ^* state and bright ππ^* state of BenzU are calculated in several solvents. The solvent dielectric constant and hydrogen bond between BenzU and protic solvent both have effects on ΔE. And the fluorescence quantum yields of BenzU are linear response to ΔE. Furthermore, we find that the more hydrogen bonds are formed between BenzU and protic solvent, the higher ΔE and fluorescence intensity are obtained.